2006
DOI: 10.1007/s00216-005-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient pseudo-isotachophoretic stacking in analysis of plasma for homocysteine by capillary zone electrophoresis

Abstract: An analytical procedure enabling routine analysis of human plasma for total homocysteine has been developed and validated. The method includes reduction of homocysteine disulfides to thiol with tris 2-carboxyethylphosphine, derivatization of the thiol with 2-chloro-1-methylquinolinium tetrafluoroborate, separation of homocysteine 2-S-quinolinium derivative from those of plasma endogenous and exogenous thiol derivatives by capillary zone electrophoresis, and quantitation with the use of ultraviolet detection ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…The analytical criteria (precision, accuracy) are comparable with those obtained by analogous methods. [12][13][14]21,22 We conclude that this method may find application in the routine analysis of blood plasma samples in experimental and clinical laboratories. Further improvement of the deproteinization approaches based on ultracentrifugation or solid-phase extraction may facilitate sample preparation and speed up the process.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The analytical criteria (precision, accuracy) are comparable with those obtained by analogous methods. [12][13][14]21,22 We conclude that this method may find application in the routine analysis of blood plasma samples in experimental and clinical laboratories. Further improvement of the deproteinization approaches based on ultracentrifugation or solid-phase extraction may facilitate sample preparation and speed up the process.…”
Section: Discussionmentioning
confidence: 80%
“…A few rather sensitive HPLC approaches (LOD < 1 μM) were also proposed in which the application of reagents, such as 2-chloro-1-methylquinoline tetrafluoroborate (CMQT), 8 1,1′-thiocarbonyldiimidazole (TCDI), 9 4,4′-dithiodipyridine 10 and 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB) 11 made it possible to use conventional UV-detectors. Later approaches based on CE-UV with the use of CMQT 12,13 and TCDI 14 were proposed. Although these approaches had a lower sensitivity, they had a number of advantages compared to HPLC such as high performance, selectivity (specificity) and affordability.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a 10 000-130 000-fold improvement in the limits of detection, which makes it feasible to analyze low-picomolar concentrations of DNA, amino acids, and proteins within 2-8 min. A third paper described used pseudotransient isotachophoretic to increase sensitivity of homocysteine detection in plasma samples using commercial CE systems and UV detection (38). Here, acetonitrile was added to the sample containing high concentration of salts (e.g., plasma).…”
Section: Processes Prior To Cementioning
confidence: 99%
“…Based on 3δ blank /k (where δ blank is the standard deviation of the blank solution and k is the slope of the calibration plot), the limit of detection (LOD) was attained of 12.5 nM. A comparison of the analytical performances with that previously reported methods [4][5][6]8,11,13,15,[30][31][32][33][34][35] for the determination of L-Cys is summarized in Table 2. As can be seen from the table, the present method is an ideal candidate for L-Cys analysis.…”
Section: Fluorescent Detection Of L-cys Via Rb1mentioning
confidence: 99%
“…Therefore, identifying and quantifying L-Cys is very important and considerable efforts have been made to develop high efficient methods for its determination [4][5][6]. Common separation techniques such as high performance liquid chromatography (HPLC), capillary electrophoresis (CE) and gas chromatography (GC), coupled with fluorescence or electrochemical detection, are usually utilized for assaying L-Cys, but they are often inconvenient to operate and often require time consuming sample preparation and separation procedures [7,8]. Because L-Cys possesses a very low molar absorptivity and lacks a suitable chromophore, derivatization with fluorescent reagents is typically used for detection [9].…”
Section: Introductionmentioning
confidence: 99%